2010
DOI: 10.1016/j.eurpsy.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence of major depression in Estonia. Results from the 2006 Estonian Health Survey

Abstract: The point prevalence of major depressive episodes was comparable with the results of other population surveys, being a little higher than the average. Age, income, ethnicity, health status, self-rated health, and previous depressive episode were independent associates of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
2
7
1
2
Order By: Relevance
“…This contrasts with previous studies from Estonia that found significant ethnic differences in SRH 34. Unhealthy behaviours35 and more frequent depression36 explained part of these inequalities but it is not known whether changes in these factors may underlie the positive health trend among the non-titular ethnic group seen in our study. Compared to Estonia and Lithuania, inequalities in less-than-good SRH were much smaller and remained unaltered during 2004–2010 in Finland which corresponds to the findings from previous studies31 37 reporting relatively stable socioeconomic disparities in health across time in the Nordic countries.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with previous studies from Estonia that found significant ethnic differences in SRH 34. Unhealthy behaviours35 and more frequent depression36 explained part of these inequalities but it is not known whether changes in these factors may underlie the positive health trend among the non-titular ethnic group seen in our study. Compared to Estonia and Lithuania, inequalities in less-than-good SRH were much smaller and remained unaltered during 2004–2010 in Finland which corresponds to the findings from previous studies31 37 reporting relatively stable socioeconomic disparities in health across time in the Nordic countries.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, the diagnostic distribution of patients treated with ECT in the Baltic states differs greatly from Scandinavian practice, in which depression is the main indication, but is similar to that found in Hungary (Gazdag et al 2004) and Turkey (Saatcioglu and Tomruk 2008). Estonia ' s relatively low ECT utilization rate in the treatment of affective disorders is somewhat surprising in the light of its relatively high rate of depression (Kleinberg et al 2010) and suicide (Suicide rates by country, 1950 -2011).…”
Section: Discussionmentioning
confidence: 82%
“… Beutel et al (1999) reported that infertile men at relatively young ages had high scores of depression. However, other studies reported high prevalence of depression observed in men at 40 years or older ( Kleinberg, Aluoja, & Vasar, 2010 ; Nicolosi et al, 2011 ). Results from the current study demonstrate that a high prevalence of depressive symptoms (23.3%) was observed in participants younger than 30 years, while anxiety symptoms was more frequently seen in participants older than 40 years (12.7%).…”
Section: Discussionmentioning
confidence: 89%